Anxiety reactivity and anxiety perseveration represent dissociable dimensions of anxiety vulnerability: A replication and extension. (10th July 2013) - Rudaizky, Daniel; MacLeod, Colin
Abstract: Trait anxiety is a unitary construct reflecting individual differences in the tendency to experience anxious symptomatology, typically measured with questionnaires such as the Spielberger Trait Anxiety Inventory (STAI‐T). Recent research by Rudaizky, Page, and MacLeod has found evidence that two different dimensions of trait anxiety account for independent variance in trait anxiety scores. These dimensions are anxiety reactivity (AR), reflecting the probability of experiencing an anxious reaction, and anxiety perseveration (AP), reflecting the persistence of anxious symptoms once elicited. There are two key issues addressed in this study: first, the replicability of Rudaizky et al.'s findings and second, the ability of the measures of AR and AP developed by Rudaizky et al. to predict independent variance in STAI‐T scores after statistically controlling for variance shared with a measure of depression. Regression analysis determined that AR and AP do account for independent variance in STAI‐T trait anxiety scores even after statistically controlling for depression. The implications of these findings for the understanding of anxiety vulnerability are discussed.